2015
DOI: 10.1242/jcs.118703
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Controls Tight Junction Formation Through Differential Regulation of Claudin Recruitment

Abstract: IQGAP1 is a scaffolding protein previously implicated in adherens junction formation. However, its role in the establishment or maintenance of tight junctions (TJs) has not been explored. We hypothesized that IQGAP1 could regulate TJ formation by modulating the expression and/or localization of junctional proteins, and we systematically tested this hypothesis in the model Madin-Darby canine kidney (MDCK) cell line. We find that IQGAP1 silencing enhances a transient increase in transepithelial electrical resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 56 publications
(77 reference statements)
2
28
0
Order By: Relevance
“…That is the case of aPKC in the PAR “polarity complex.” 65-67 Likewise, ERK1/2 controls expression of TJ proteins, 68 and junction formation 69,70 . Furthermore, JNK has been shown to be part of a pathway that modulates trans-epithelial resistance 71 and ZO-1 assembly 72 . Loss of K76 results in increased skin permeability via loss of claudin 1 73 .…”
Section: Keratins In Signalingmentioning
confidence: 99%
“…That is the case of aPKC in the PAR “polarity complex.” 65-67 Likewise, ERK1/2 controls expression of TJ proteins, 68 and junction formation 69,70 . Furthermore, JNK has been shown to be part of a pathway that modulates trans-epithelial resistance 71 and ZO-1 assembly 72 . Loss of K76 results in increased skin permeability via loss of claudin 1 73 .…”
Section: Keratins In Signalingmentioning
confidence: 99%
“…In addition, our study showed that cell junctions involving VE‐cadherin and claudin‐5 are altered after IQGAP1 treatment during the processes of endothelial cell injury to recovery. Furthermore, previous studies showed that IQGAP1 mediates barrier function changes by regulating the tight junctions and adherens junctions of endothelial cells . Some studies reported that after the knockdown of IQGAP1, the morphology and function of vascular endothelial cells were altered, indicating that a decrease in IQGAP1 was the cause of endothelial barrier dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…The Imatinib has no significant effect on TEER, monolayer permeability, cell migration and PDGFRβ/PI3K/Akt/IQGAP1 pathway activity of HUVECs (Figure S1 regulating the tight junctions and adherens junctions of endothelial cells. [46][47][48][49] Some studies reported that after the knockdown of IQGAP1, the morphology and function of vascular endothelial cells were altered, indicating that a decrease in IQGAP1 was the cause of endothelial barrier dysfunction. 11 Similarly, we found that SV/ SV-NPs up-regulated the expression of IQGAP1.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 alters TJ assembly by reducing the recruitment of claudin 2 and increasing the assembly of claudin 4 into TJ complexes. It also diminishes barrier function by inhibiting the Cdc42-JNK signaling pathway [ 115 ]. Conversely, RNase-L promotes the expression of TJ proteins claudin 1 and occludin, enhances barrier function, and prevents the transepithelial migration of pathogens such as EPEC [ 84 ].…”
Section: Rnase-l and The Cytoskeletonmentioning
confidence: 99%